Neuroeconomic Studies of Impulsivity: Now or Just as Soon as Possible? - Glimcher, Paul William; Kable, Joseph; Louie, Kenway (American Economic Review, 2007)
Neuroeconomic Studies of Impulsivity: Now or Just as Soon as Possible? by Paul William Glimcher, Joseph Kable and Kenway Louie. Published in volume 97, issue 2, pages 142-147 of American Economic Review, May 2007